Analysis of Rainfall on the Production of Sidimpuan Snake Fruit (Salacca sumatrana Becc.) in South Tapanuli Regency - Harahap, Imelda Sari (Jurnal Ar Ro'is Mandalika (Armada), 2026)
Rainfall is one of the climatic elements that directly influences agricultural production; moreover, it often becomes a limiting factor in crop productivity. This study aims to analyze the effect of rainfall on the production of Sidimpuan snake fruit (Salacca sumatrana Becc.) in East Angkola and West Angkola Districts, South Tapanuli Regency. This research employed a survey method. The research data consisted of secondary data, including rainfall data and Sidimpuan snake fruit production data from 2014 to 2023 in East Angkola and West Angkola Districts, South Tapanuli Regency. Data were collected using purposive sampling techniques. The data were analyzed using regression and correlation analyses, presented in the form of tables and graphs, and described descriptively. The results show that rainfall in East Angkola District, South Tapanuli Regency, has a negative effect on the production of Sidimpuan snake fruit, with a regression coefficient of r = 0.4, indicating a weak relationship between rainfall and Sidimpuan snake fruit production. The contribution of rainfall is 19%, while 89% of Sidimpuan snake fruit production in East Angkola District, South Tapanuli Regency, is influenced by other factors not examined in this study. Meanwhile, the regression analysis for rainfall in West Angkola District, South Tapanuli Regency, shows a positive effect on Sidimpuan snake fruit production, with a regression coefficient of r = 0.5, indicating a moderate relationship between rainfall and Sidimpuan snake fruit production. The contribution of rainfall is 21%, while 79% of Sidimpuan snake fruit production in West Angkola (Sipirok) District, South Tapanuli Regency, is influenced by other factors not examined in this study.